Histopathological confirmation of disseminated larvae (iL3) of Strongyloides ratti in an immunosuppressed Wistar rat - Mahmuda, Aliyu; Al-Zihiry, Khalid Jameel Kadhim; Abd Majid, Roslaini; Awang Hamat, Rukman; Abdulhaleem, Noor; Bande, Faruku; Mohammed, A. A.; Alayande, Musbaudeen Olayinka; Unyah, Ngah Zasmy (Malaysian Society of Parasitology and Tropical Medicine, 2017)
Human strongyloidiasis research requires a large supply of Strongyloides stercoralis.This can be achieved through in vivo maintenance of Strongyloides stercoralis in Merionesunguiculatus, but isolating a large quantity of Strongyloides stercoralis to establish thecolony from an infected patient is too difficult to achieve. Hence, Strongyloides ratti havebeen used as a model in human strongyloidiasis research. This study describes a successfulestablishment and maintenance of Strongyloides ratti infection in experimentallyimmunosuppressed Wistar rats. Large quantities of filariform (iL3) larvae of Strongyloidesratti for research related to human strongyloidiasis have been harvested following thisprotocol. Molecular detection method based on PCR using species specific primers was usedto confirm the species of the harvested infective larvae (iL3). Additionally, the identificationof histopathological lesions confirmed the presence of infective larvae (iL3) in the liver andlungs as a result of an increased parasite burden due to hyperinfection and disseminateddisease. This pathological presentation was found to be similar to that reported inStrongyloides stercoralis-infected immunocompromised human subjects.